Lignocaine/phenylephrine nasal spray vs. placebo for the pain and distress of nasogastric tube insertion in children: A study protocol for a randomized controlled trial - Craig, S.; Seith, R.; Cheek, J.; West, A.; Wilson, K.; Egerton-Warburton, Diana (BioMed Central Ltd., 2015)
Background: Patients and clinicians consistently rate insertion of a nasogastric tube (NGT) as one of the most painful and distressing emergency department procedures. Despite this, surveys of emergency clinicians suggest that provision of adequate procedural analgesia is often inconsistent and suboptimal. While many studies have demonstrated the effectiveness of various interventions to reduce pain and distress in adults, there have been few studies in the pediatric population. There are currently no studies comparing the effectiveness of a local anesthetic nasal spray for the prevention of the pain and distress associated with NGT insertion in children. This study aims to compare the analgesic efficacy of a proprietary preparation of lignocaine/phenylephrine nasal spray and placebo for this indication. Methods/Design: This is a prospective, randomized, controlled, double-blind superiority trial of 100 children aged 6 months to 5 years weighing at least 6 kg in whom a nasogastric tube is planned to be inserted. These children will be randomized to either intranasal lignocaine/phenylephrine or placebo. Pain severity is the primary outcome measure and will be measured utilizing the Face, Legs, Arms, Cry and Consolability (FLACC) pain severity rating scale. An independent staff member not involved in inserting the NGT and the child's parents or carer will also record pain and distress on a visual analog scale (VAS). FLACC scores and VAS scores will be presented as median and interquartile range (IQR). Non-normally distributed scores will be compared using a Wilcoxon rank-sum test. Categorical data will be analyzed using Fisher's exact test. Adverse events will be described as type and incidence. Discussion: Previous studies on NGT insertion have not focused on the pediatric population. This study aims to establish the effectiveness of a simple intranasal spray of lignocaine/phenylephrine in children undergoing NGT insertion. A positive result of this study would provide evidence of an effective intervention in a procedure considered by many to be very painful and distressing.